2013
DOI: 10.1039/c2gc36556a
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of feather keratin in ionic liquids

Abstract: Keratin from various livestock industries is currently a waste material that has potential as a source of polyamide polymers that could replace fossil fuel derived materials if processing methods can be developed. In this work we have investigated methods for the dissolution and regeneration of keratin. Dissolution of keratin (from turkey feather) in ionic liquids was conducted under nitrogen at 130 °C for 10 hours. It was found that [BMIM]Cl, [AMIM]Cl and [choline][thioglycolate] could dissolve turkey feather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
183
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(195 citation statements)
references
References 43 publications
10
183
2
Order By: Relevance
“…3 The ATR−FTIR spectra of the samples were shown in Figure 5 bending). 12 Figure 5A showed that no new functional groups appeared in the extracted keratin. Therefore, dissolution in the alkali solution did not strongly affect the peptide bonds of the feather keratin.…”
Section: Extraction Of Keratin From Feathers Assisted By Sfementioning
confidence: 96%
See 1 more Smart Citation
“…3 The ATR−FTIR spectra of the samples were shown in Figure 5 bending). 12 Figure 5A showed that no new functional groups appeared in the extracted keratin. Therefore, dissolution in the alkali solution did not strongly affect the peptide bonds of the feather keratin.…”
Section: Extraction Of Keratin From Feathers Assisted By Sfementioning
confidence: 96%
“…3 Feathers are readily available, low cost, renewable, and biodegradable, making them dependable biopolymer feedstock that should have similar properties to polyamides. 4,5 In recent years, researchers are looking for new applications of feather materials, such as food or compostable packaging, 2,6 edible film, 7 biosorbents, 8 and other composites. 9 Keratins have plenty of intermolecular and intramolecular cystine cross-links, which distinguishes them from other fibrous proteins such as collagen and myofibrillar protein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…All physical and spectroscopic data of the ILs used for the experiments were found to be in accordance to reported values [12][13][14][15][16][17][18][19][20][21].…”
Section: Vinlylated Imidazolium Saltsmentioning
confidence: 63%
“…Commercial 1-allyl-3-methylimidazolium chloride, CAS registry number [65039-10-3], was purchased from IoLiTec, Germany, or prepared by alkylation of 1-methylimidazole with allyl chloride according to published standard procedures [12]. Commercial 1-allyl-3-methylimidazolium tetrafluoroborate, CAS registry number [851606-63-8], was derived from 1-allyl-3-methylimidazolium chloride [65039-10-3] by extractive anion metathesis according to literature procedures [13,14].…”
Section: Allylated Imidazolium Saltsmentioning
confidence: 99%
“…Therefore, aqueous solutions of chaotropic reagents such as urea or guanadinium hydrochloride are also needed to bring the bulk of the soluble proteins into solution [18][19][20] . There are reports of ionic liquids being used to solubilize keratin materials through breaking intermolecular disulfide and hydrogen bonds within keratin proteins [21][22][23][24][25] .…”
Section: Extraction Of Keratins and Fabrication Of Materialsmentioning
confidence: 99%